DAMPAK PERTUMBUHAN EKONOMI NASIONAL TERHADAP PEMBENTUKAN GAS RUMAH KACA DAN PENURUNAN KAPASITAS SEKTOR EKONOMI DI INDONESIA: PENDEKATAN ANALISIS INPUT-OUTPUT - SUPENA FRIYATNO; BUNASOR SAMIN; NIZWAR SYAFA’AT (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
It has been proven that national economic growth which is originally expected toimprove people welfare, to balance the gaps of income, to alleviate poverty and to keepthe environmental stability could not accomplish the goal of economic development.The objectives of this research are: (1) to analyze the impact of national economicgrowth on greenhouse gases formation, especially on emission of carbon, sulphur andnitrogen, (2) to analyze the impact of greenhouse gases emission which is formed byeconomic activities as consequences of national economic growth on the capacity ofeconomic sectors, especially in declining capacity on output, income, value added andemployment. To prove those main objectives, the national Input-Output analysis is usedin this research. The data used in this research are input-output transaction matrix year1980, 1985, 1990, 1995 and 2000 which is published by Statistical Center Agency(BPS). Input-Output data analysis showed that with 4.24% of economic growth scenarioformed carbon, sulphur, and nitrogen each equal to 3,276.6 kilo ton, 44.2 kilo ton, and79.9 kilo ton respectively. By internalizing the price of carbon Rp 190,000 per mt, theywould decline the capacity of economic sectors, such as Rp 1.4 triliun of output, Rp187.9 biliun of income, Rp 657.2 biliun of value added and 33.728 persons ofemployment respectively. In conclusion, economic growth has caused the greenhousegaseous formation, and has implication on cost of externalities on environment.Furthermore, the policies to compensate the recovery of environmental degradation areneeded through some instruments of policies, such as command-and-control, and basedmarket-policies in Indonesia.